Pengaruh Keragaman Produk, Kualitas Produk Dan Pelayanan Terhadap Keputusan Pembelian Kon-Sumen Pada Jaya Collection - Fathan Muhammad, Rabhi (Fakultas Ekonomi Universitas Gresik, 2023)
This study aims to determine the effect of product diversity, product quality, and service quality on purchasing decisions for Yaya Collection consumers in Trosono Village, Parang District, Magetan Regency. The population in this study are followers of the Yaya Collection Instagram account (@my_Collection.kuu), which currently has 2,416 followers. Samples taken according to the Rao Purba formula were 100 consumers. The research method uses multiple linear regression analysis method. The results of this study indicate that product diversity has no effect on the purchase decision of the Yaya Collection. In addition, product diversity also has no effect on purchasing decisions. Product quality has a positive effect on consumer purchasing decisions, which means that the better the quality of a product, the higher the level of consumer purchasing decisions. The results of the study indicate that there is a significant influence between service quality variables on the Yaya Collection purchasing decision. In addition, the results show that there is a significant influence between the variables of product diversity, product quality, and service quality on the purchasing decision of the Yaya Collection